Foresighting future oceans: Considerations and opportunities. (June 2022) - Kelly, Rachel; Foley, Paul; Stephenson, Robert L.; Hobday, Alistair J.; Pecl, Gretta T.; Boschetti, Fabio; Cvitanovic, Christopher; Fleming, Aysha; Fulton, E.A.; Nash, Kirsty L.; Neis, Barbara; Singh, Gerald G.; et al.
Abstract: Climate change, overexploitation, pollution, and other pressures continue to degrade and threaten the marine environment and associated systems. Successfully managing and governing marine socioecological systems in light of these compounding pressures requires approaches that move beyond reactive and business-as-usual responses. Specifically, achieving ocean health and sustainability in these socioecological systems requires strengthening and applying processes that proactively imagine alternatives and plan for preferred futures. This paper contributes to emerging dialogue on the need to co-create visions of ocean futures, with a focus on the concept of foresighting. Foresighting is a process of creatively identifying possible, plausible, alternative socioecological futures in the medium to long term, and is increasingly seen as an approach that can support decision-making under uncertainty about the future. Here, we explore the origins and practical applications of foresighting from across the literature, before focusing on its (potential) application in the marine context. We discuss which elements are potentially useful or require more engagement to facilitate the visioning of shared futures for marine socioecological systems. We consider key dimensions of foresighting that require greater attention, including futures literacy, inclusivity, and inter- and transdisciplinarity. We also highlight important issues for consideration, including whether foresighting efforts should be informed by experts or by broader community participation, and discuss potential ethical issues associated with engaging marine stakeholders in foresighting. We determine that foresighting has considerable potential in the marine context for connecting stakeholder groups in the process of imagining and shaping equitable and sustainable ocean futures, but several methodological and ethical issues – including who gets to participate, and how - require further critical and careful consideration to create conditions for success.